INTENSITASSERANGAN PENYAKIT BLAS (Pyricularia oryzae Cav.) PADA PADI LAHAN PASANG SURUT DI DESA SUNGAI ITIK KECAMATAN SUNGAI KAKAP - Herly Annisa; Sarbino Sarbino; Fadjar Rianto (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRACTPyricularia oryzaeis one of the important pathogen in rice. Blast disease can decreasing the yield of rice production in various countries in the world. This study aims to determine diease incidence and disease severity of blast at Desa Sungai Itik, both in leaves and panicles. This research was conducted from July to December 2017. The research was conducted in Desa Sungai Itik Kecamatan Sungai Kakap Kabupaten Kubu Raya. The variables used were disease severity and disease insidence both on leave and panicle.Blast disease was found both at leave and panicles. The disease severity of leaf between 51,85% - 59,25% and at panicle 48,87% - 71.35%. There was a positive correlation between leaf blast and neck blast.Keywords: Disease Insidence, Disease Severity, Correlation, Pyricularia oryzae, Rice.